The Direct Employment Impact of Public Investment - Moszoro, Marian (Washington, D.C. : International Monetary Fund, 2021)
We evaluate the direct employment effect of the public investment in key infrastructure-electricity, roads, schools and hospitals, and water and sanitation. Using rich firm-level panel data from 41 countries over 19 years, we estimate that USD 1 million of public spending in infrastructure create 3-7 jobs in advanced economies, 10-17 jobs in emerging market economies, and 16-30 jobs in low-income developing countries. As a comparison, USD 1 million public spending on R and D yields 5-11 jobs in R and D in OECD countries. Green investment and investment with a larger R and D component deliver higher employment effect. Overall, we estimate that one percent of global GDP in public investment can create more than seven million jobs worldwide through its direct employment effects alone.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock; Underground Econom